UPAYA OPTIMALISASI KINERJA ACCOUNT REPRESENTATIVE DALAM MENINGKATKAN KEPATUHAN WAJIB PAJAK DI KECAMATAN BOROBUDUR - Siagian, Sutan Pangeran Panangian; Syaflan, Meidi; Setyawati, Rufaida (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2024)
The purpose of this study is to determine and analyze Account Representative Performance and what factors affect Account Representative Performance in increasing taxpayer compliance in Borobudur District, and Account Representative efforts to improve taxpayer compliance in Borobudur District. The type of this research is descriptive research with a qualitative approach. Primary data is taken directly from the research location through interviews (Indeepth Interview) to respondents, secondary data is in the form of written documents from the Government, such as secondary data about the organizational structure of the Magelang Tax Office. The data analysis technique used in this study is an interactive model of analysis, consisting of data reduction, data presentation and conclusion drawing. The results showed that the performance of Account Representatives at Magelang Tax Office with an imbalance between the number of Account Representatives and the number of Taxpayers could still be handled properly by the Account Representative. The existence of ability, communication, initiative, punctuality and good quality of work as well as a good individual and organizational environment strongly supports the implementation of the work program that has been planned and is able to achieve its targets.